Bank Ownership and Credit over the Business Cycle : Is Lending by State Banks Less Procyclical? - Bertay, Ata Can; Demirguc-Kunt, Asli; Huizinga, Harry (World Bank, Washington, DC, 2014)
This paper finds that lending by state banks is less procyclical than lending by private banks, especially in countries with good governance. Lending by state banks in high-income countries is even countercyclical. On the liability side, state banks expand potentially unstable non-deposit liabilities relatively little during booms, especially in countries with good governance. Public banks also report loan non-performance more evenly over the business cycle. Overall the results of the analysis suggest that state banks can play a useful role in stabilizing credit over the business cycle as well as during periods of financial instability. However, the track record of state banks in credit allocation remains quite poor, questioning the wisdom of using state banks as a short-term countercyclical tool.